Motivation and Retention of Millennials in Fujian Province - Yang, Lujing (2016)
The dissertation attempts to address the lacuna of research on the motivation and retention of the millennials in Fujian, China. The study explains the various socio-cultural issues and economic conditions involved in dealing with the application of theories of motivation and retention to the cases in Fujian. The study in undertaken in the service industry of Fujian Province in China. This dissertation identifies that the leadership style and organisational structure are primarily responsible for understanding the job-hopping behaviour and motivation among the millennials. It is also found that this generation is a very vibrant and intrinsically motivated set of individuals who consider personal growth and development more important than job security. The results are based on a sample of twenty-one respondents, of which, seventeen are the millennials from post- 80s and post-90s age cohort in Fujian. The remaining four are the managers working in the service industry. The study uses the non-probability sampling method (snowball sampling) to select this sample. The major recommendations of the study are; to improve a cross-generational interaction platform to convert the workspace into a more dynamic and a creative place. Second, a more flexible work culture can retain more millennials at the job. Third, intensive training and leadership development programmes should be constituted to address the challenges faced by the human resource management in tapping this vast potential of the millennials.